2017
DOI: 10.1055/s-0037-1603755
|View full text |Cite
|
Sign up to set email alerts
|

The Rationale of Osteotomy around the Knee

Abstract: Frontal plane varus or valgus deformity causes overload in the ipsilateral compartment and may induce and accelerate cartilage damage. Osteotomy around the knee should be considered in symptomatic constitutional and posttraumatic metaphyseal deformities of more than 3-degree deviation. Age, grade of osteoarthritis, obesity, and nicotine consumption are no exclusion criteria for osteotomy. For correction of varus deformity, biplanar open wedge osteotomy of the tibia with fixation by a plate fixator has proven t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 55 publications
0
31
0
2
Order By: Relevance
“…[24][25][26]32 If the obliquity of the joint line is changed more than 4 degrees compared with normal, a double-level osteotomy maybe the better option. 24 However, we have included these with deformities located in anatomical structures other than tibia alone in purpose. It seems these patients do not meet the inclusion criteria for HTO.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26]32 If the obliquity of the joint line is changed more than 4 degrees compared with normal, a double-level osteotomy maybe the better option. 24 However, we have included these with deformities located in anatomical structures other than tibia alone in purpose. It seems these patients do not meet the inclusion criteria for HTO.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that DFO is the treatment for around 20% of coronal plane deformities. 2 We would agree that, even in the author's own practice, the distal femur makes up a smaller proportion of the cause of coronal plane deformity for medial compartment defects and is performed to a far less degree than the HTO. Typically, this is seen in posttraumatic cases 3 with developmental medial compartment injury, whereas DFO is more frequently indicated for lateral compartment injury and treated by an opening lateral wedge or a closing medial wedge osteotomy at the distal femur.…”
mentioning
confidence: 89%
“…23 It is important recognize that, although most would agree that age should be a factor, specific cultures should be respected such as in Asia where the active stage of life may be extended. 2 Furthermore, results from Asia have proved that age should not be an exclusion criterion for an osteotomy. 24 Bonasia et al specify range of motion >90 degrees and flexion contracture <15 degrees, along with proposed angular correction of less than 20 degrees as being associated with positive outcomes.…”
Section: History and Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…But obviously basic principles change here. 2,9 Nowadays, with increasing knowledge and data from high-quality studies over the last 2 decades, a more individual approach and treatment strategy is necessary in the treatment of osteoarthritis, in particular based on anatomical and functional factors such as type, location, extent and etiology of deformity, knowledge of kinematics and instabilities, respect and knowledge of the importance of the joint line, and consequently avoidance of iatrogenic deformities and overcorrection. Together with patient specific factors, this approach will result in an optimized individual treatment strategy for osteoarthritic knees.…”
Section: See Related Article On Page 638mentioning
confidence: 99%